Structural and electrochemical properties of recycled active electrodes from spent lead acid battery and modified with different manganese dioxide contents. (1st April 2018) - Rada, S.; Cuibus, D.; Vermesan, H.; Rada, M.; Culea, E.
Abstract: Samples of MnO2 incorporated into active electrodes structure of the disassembled car batteries were prepared by classical melt-quenching method. The effect of MnO2 concentration on host network were investigated by X-ray diffraction (XRD) analysis, InfraRed (IR), UltraViolet-Visible (UV–Vis), Photoluminescence (PL) and Electron Paramagnetic Resonance (EPR) spectroscopy, measurements of Cyclic Voltammetry (VC). X-ray diffractograms show the presence of the metallic lead in the cubic structure and small amounts of PbO2 crystalline phase with the orthorhombic structure in the metallic samples. Combining all of the outputs from different characterizations, we can conclude that the amount of MnO2 incorporated into structure of the recycled active electrodes has effect on the number of non-bridging oxygen atoms that determines the role of MnO2 as a modifier/network former. At lower MnO2 contents, the doping breaks PbOPb bonds producing the formation of [MnO6 ] structural units in which the Mn +2 ions are in octahedral symmetry, gap energy value increases and the effect of luminescence is quenched. At higher MnO2 content, MnO2 plays a network former role, joins the vitroceramic network as [MnO4 ] and [MnO6 ] structural units and the PL intensity increases. The sample doped with small MnO2 content (x = 5mol%) used as working electrode in the measurements of cyclic voltammetry shows a good reversibility of the voltammogram, also improved the electrochemical properties, namely an increased stability in acidic electrolyte environments and offers an alternative for obtaining of electrodes for rechargeable batteries.